2009
DOI: 10.1128/iai.01335-08
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Typhimurium Mutants Unable To Convert Malate to Pyruvate and Oxaloacetate Are Avirulent and Immunogenic in BALB/c Mice

Abstract: Previously, we showed that the Salmonella enterica serovar Typhimurium SR-11 tricarboxylic acid (TCA) cycle must operate as a complete cycle for full virulence after oral infection of BALB/c mice (M. Tchawa Yimga, M. P. Leatham, J. H. Allen, D. C. Laux, T. Conway, and P. S. Cohen, Infect. Immun. 74:1130-1140, 2006). In the same study, we showed that for full virulence, malate must be converted to both oxaloacetate and pyruvate. Moreover, it was recently demonstrated that blocking conversion of succinyl-coenzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…For instance, deletions in the pyruvate pathway have been shown to alter the SPI1-mediated gene expression and infectivity of the Salmonella enterica serovar typhimurium (79). Furthermore, it has been reported that Salmonella mutants that are unable to convert malate to pyruvate and oxaloacetate are avirulent and immunogenic in BALB/c mice (80) and that an incomplete TCA cycle increases the survival of Salmonella during infection (81). Moreover, in Pseudomonas aeruginosa, mutations in TCA cycle enzymes have been shown to affect the type III secretion system of the pathogen (82), and regulators of Staphylococcus aureus responding to TCA cycle-associated metabolic changes have also been implicated in virulence control (83).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, deletions in the pyruvate pathway have been shown to alter the SPI1-mediated gene expression and infectivity of the Salmonella enterica serovar typhimurium (79). Furthermore, it has been reported that Salmonella mutants that are unable to convert malate to pyruvate and oxaloacetate are avirulent and immunogenic in BALB/c mice (80) and that an incomplete TCA cycle increases the survival of Salmonella during infection (81). Moreover, in Pseudomonas aeruginosa, mutations in TCA cycle enzymes have been shown to affect the type III secretion system of the pathogen (82), and regulators of Staphylococcus aureus responding to TCA cycle-associated metabolic changes have also been implicated in virulence control (83).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomycin-treated mice have been used since 1954 to overcome the colonization resistance that prevents colonization of conventional animals by experimentally introduced enteric bacteria (7). We have made extensive use of the streptomycin-treated mouse model to study nutritional factors that govern colonization of the mouse large intestine by E. coli and Salmonella enterica serovar Typhimurium (3,8,16,18,30,31,34,35,48,49,51,52). Treatment of mice with streptomycin selectively removes facultatively anaerobic E. coli bacteria, enterococci, streptococci, lactobacilli, and anaerobic lactobacilli and bifidobacteria without changing the overall populations of anaerobes, including Bacteroides and Eubacterium (25).…”
Section: Methodsmentioning
confidence: 99%
“…2-Hydroxybutyrate, the metabolic product of threonine, also was found up-regulated in our results. Ornithine acted as a precursor into the immune response (Mercado-Lubo et al, 2009). Glutamate can stimulate the immune system and aspartate is an incomplete degradation product of glutamate in immune cells (Yoshida et al, 1987).…”
Section: The Effect Of Ee On Systemic Metabolitesmentioning
confidence: 99%